KELAYAKAN BAHAN AJAR MODUL PADA MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Julia Inka Sari; Syamswisna Syamswisna; Yokhebed Yokhebed (Universitas Tanjungpura, 2019)
AbstractThis research aimed to determine the feasibility of module biodiversity material as teaching materials at class X high school. CVR analysis according Lawshe Method with a Likert Scale . The selection validators is done by purposive sampling technique. The validation includes instrument validation and module teaching material validation. Validation of the module instrument is validated by 2 lecturers in the field of Biology who understand about making teaching materials and 1 biology teacher. Validator module teaching materials consist of 2 lecturers in Biology Education and 3 of biology class X high school teachers. Aspects assessed in the validation stage include 4 aspects, namely the feasibility of content, language, presentation, and graphics. Based on the results the analysis all aspects of the module feasibility assessment, the CVI value of 0.96 was obtained. Valid categories are founded in all criteria in the aspects of content, linguistics and presentation, while invalid categories is founded in one of the six criteria in graphic aspects with a CVR value of 0.6, namely the criteria for drawing or graphic attractiveness. The implementation of modules in learning could be done after improvements to invalid criteria. Keywords: inventory, modules, medicinal plants